Coexistence of Ameloblastoma and Odontogenic Keratocyst - A Case Report - Sunila Thomas; Anita Balan (Wolters Kluwer Medknow Publications, 2007)
There are conflicting opinions about the origin of ameloblastoma, probably one of the most controversial neoplasms, from an odontogenic cyst (mural ameloblastoma). A unique case of ameloblastomatous transformation of an Odontogenic Keratocyst, an extremely rare phenomenon is reported.